Elemental Analysis of Sea, Rock, and Bamboo Salts by Inductively Coupled Plasma-Optical Emission and Mass Spectrometry. (21st November 2016) - Hwang, In Min; Yang, Ji-Su; Kim, Sung Hyun; Jamila, Nargis; Khan, Naeem; Kim, Kyong Su; Seo, Hye-Young
ABSTRACT: The present study reports the determination of mineral nutrients and toxic elements of sea, rock, and roasted bamboo salts from China, India, France, Australia, Nepal, Argentina, and South Korea. Mineral nutrients including macro (Ca, K, Mg, Na, and S), micro (B, Cu, Fe, Sr, Mn, and V), trace (Ba, Be, Co, Cr, Ga, Li, Ni, Rb, Se, and Zn), and toxic (Al, Cd, Cs, In, Pb, and Tl) elements were analyzed by inductively coupled plasma-optical emission spectroscopy (ICP-OES) and ICP-mass spectrometry (ICP-MS). The detection limits were from 7.032 (Mg) to 13.915 (S) and 0.023 (Sr) to 0.228 (Ba) ng/g for ICP-OES and ICP-MS, respectively. The recoveries for fortified samples were from 91.3 to 107.6%. The concentrations of B, Ba, Be, Cs, Ga, In, Rb, Tl, and V were reported for the first time. In terms of mineral nutrients, the order was roasted salt > sea salt > rock salt. In addition, the only toxic element in roasted bamboo salt was aluminum. The concentrations of the elements were comparable to literature values and met regulatory guidelines. Roasted bamboo salt was shown to be a rich source of nutrients and provided the lowest concentrations of toxic elements. All salt types were shown to be safe for human consumption.